Mindful teacher, mindful school : improving wellbeing in teaching & learning Author - Hawkins , Kevin (Los Angeles, 2017)
Former school teacher turned mindfulness consultant Kevin Hawkins truly understands the joys of teaching and the desire to make a real difference in the lives of students, as well as the challenges and risks of burnout that most teachers experience on a daily basis. With this guide to mindful practice, teachers new and experienced can learn how to use mindfulness in their own professional and personal lives as well as how to incorporate it in their teaching to support student well-being. Combining theory with practice and illustrated with real life stories, this guide will show readers: what mindfulness is; the research and scientific evidence behind it; how changing the way you approach situations can transform the way you feel; how to manage stress, and look after yourself; how teaching mindfully can help your students; what mindfulness can do for the culture in your school. Packed with DIY exercises, activities to use in the classroom, and links to resources and further reading, this inspiring book will support experienced and new teachers to maintain a healthy work-life balance and thrive as a teaching professional. -- Provided by publisher
Keywords: Reflective teaching; Mindful (Psychology)